Catalytic revalorization of plastic waste phthalate plasticizers into simple aromatics and alkenes - Windels, Simon; Seynaeve, Nienke; Stuyck, Wouter; De Vos, Dirk E. (Frontiers in Chemical Engineering, 2024)
In order to deal with legacy additives in plastic waste streams, multiple extraction processes are being developed. For sustainability and economic reasons, these processes call for the parallel implementation of revalorisation routes for the extracted toxic compounds, especially when dealing with large volumes as in the case of phthalate plasticizers. On account of its intrinsic value, the recovery of the aromatic fragment from such end-of-life phthalate ester mixtures was prioritized in this work. To that end, a hydrolysis-decarboxylation process was designed using hydrophobic zeolites and heterogeneous Ptcatalysts, in water as a safe and environmentally benign solvent. By carefully tuning the reaction parameters, the selective formation of phthalic acid, benzoic acid or benzene can be achieved in nearquantitative yields, next to the recovery of alkene and alcohol side chain fragments (yields up to 99%).